A Mechanically Reinforced Super Bone Glue Makes a Leap in Hard Tissue Strong Adhesion and Augmented Bone Regeneration. Issue 11 (25th January 2023) - Hu, Shanshan; Wang, Shan; He, Qingqing; Li, Dize; Xin, Liangjing; Xu, Chuanhang; Zhu, Xingyu; Mei, Li; Cannon, Richard D.; Ji, Ping; Tang, Han; Chen, Tao
Abstract: Existing bone tissue engineering strategies aim to achieve minimize surgical trauma, stabilize the injured area, and establish a dynamic osteogenic microenvironment. The cutting‐edge bone glue developed in this study satisfies these criteria. Inspired by the excellent adhesive properties of mussels, herein, a super osteogenic glue (L‐DPZ) that integrates poly(vinyl alcohol), L‐dopa amino acid, and zeolitic imidazolate framework‐8 characterized by catechol–metal coordination is used to successfully adhere to hard tissue with a maximum adhesive strength of 10 MPa, which is much higher than those of commercial and previously reported bone glues. The stable hard tissue adhesion also enables it to adhere strongly to luxated or broken teeth, Bio‐Oss (a typical bone graft material), and splice fragments from comminuted fractures of the rabbit femur. Then, it is testified that the L‐DPZ hydrogels exhibit satisfactory biocompatibility, stable degradability, and osteogenic ability in vitro. Moreover, the ability to anchor Bio‐Oss and sustained osteogenesis of L‐DPZ result in satisfactory healing in calvarial bone defect models in rabbits, as observed by increased bone thickness and the ingrowth of new bone tissue. These results are expected to demonstrate solutions to clinical dilemmas such as comminuted bone fracture fixation, bone defect reconstruction, and teeth dislocation replantation. Abstract : An ultra‐high strength orthopedic adhesive to splice bone fragments and adhere bone grafts is reported, whilst also guiding subsequent bone healing. This adhesive integrates poly(vinyl alcohol), L‐dopa amino acid, and the zeolitic imidazolate framework‐8, which opens up a promising avenue for many clinical dilemmas such as comminuted fracture fixation and bone defect reconstruction.